Optimizing AI solutions for population health in primary care - Sanjay Basu; Pablo Bermudez-Canete; Tannen Christopher Hall; Pranav Rajpurkar (npj Digital Medicine)
Artificial intelligence (AI) has primarily enhanced individual primary care visits, yet its potential for population health management remains untapped. Effective AI should integrate longitudinal patient data, automate proactive outreach, and mitigate disparities by addressing barriers such as transportation and language. Properly deployed, AI can significantly reduce administrative burden, facilitate early intervention, and improve equity in primary care, necessitating rigorous evaluation and adaptive design to realize sustained population-level benefits.